2007
DOI: 10.1093/toxsci/kfm268
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite-Induced Thymus Atrophy is Mediated by Cell Cycle Arrest: A Characteristic Downregulation of E2F-Related Genes Revealed by a Microarray Approach

Abstract: Thymus atrophy is induced by a variety of chemicals, including environmental contaminants and is used as a sensitive index to detect their adverse effects on lymphocytes. In the present study we adopted a toxicogenomics approach to identify the pathways that mediate the atrophy induced by arsenite. We also analyzed gene expression changes observed in the course of thymus atrophy by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), dexamethasone (DEX), and estradiol (E2), to determine whether arsenite induces atrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
0
20
0
1
Order By: Relevance
“…Some experimental cancer therapeutics have common molecular features intended to inhibit Rb phosphorylation and E2F1 release to target the uncontrolled growth of cancer cells [Murillo et al, 2002;Hahm and Singh, 2007;Lee et al, 2007]. However, environmental toxins, such as arsenite and 2,3,7,8-tetrachloro-p-dioxin, induce cell-cycle arrest in G1 by Rb-mediated repression of E2F-dependent transcription [Puga et al, 2000;Nohara et al, 2008]. We have found that Cd-induced cell-cycle arrest in WI38 cells correlates with the hypophosphorylation of Rb, a decrease in E2F1 translocation to the nucleus, and the inhibition of E2F1 transcriptional activity in a luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some experimental cancer therapeutics have common molecular features intended to inhibit Rb phosphorylation and E2F1 release to target the uncontrolled growth of cancer cells [Murillo et al, 2002;Hahm and Singh, 2007;Lee et al, 2007]. However, environmental toxins, such as arsenite and 2,3,7,8-tetrachloro-p-dioxin, induce cell-cycle arrest in G1 by Rb-mediated repression of E2F-dependent transcription [Puga et al, 2000;Nohara et al, 2008]. We have found that Cd-induced cell-cycle arrest in WI38 cells correlates with the hypophosphorylation of Rb, a decrease in E2F1 translocation to the nucleus, and the inhibition of E2F1 transcriptional activity in a luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic heavy metals such as arsenite and mercury induce cell-cycle arrest in many cell types [Ponce et al, 1994;Nohara et al, 2008]. Cd causes G2/M arrest in Chinese hamster lung and ovarian (CHO) cells, nonsmall cell lung carcinoma (CL3) cells, murine macrophages (J774A.1), rat kidney proximal tubular epithelial (NRK-52E) cells, and murine splenic lymphocytes [Hader et al, 1996;Chao and Yang, 2001;Yang et al, 2004;Kim et al, 2005;Xie and Shaikh, 2006;Chatterjee et al, 2009].…”
mentioning
confidence: 99%
“…It has long been known to be vulnerable to atrophy associated with exposure to a variety of substances, including hormones, immunosuppressive pharmaceuticals, and environmental chemicals (Ashwell et al, 2000;Shanker, 2004;Drela, 2006;Zoller and Kersh, 2006;Nohara et al, 2008). Given the complexity of the thymus, compounds that cause thymic atrophy could be acting on a variety of cellular targets and through various mechanisms (Nohara et al, 2008), such as inhibition of thymocyte precursors in the bone marrow or fetal liver, or inhibition of intrathymic development of the thymocytes themselves (Nohara et al, 2008). These may result from indirect effects on the supporting stromal elements that produce growth factors and signals, or direct mechanisms such as decreased cell proliferation and increased cell death through apoptosis (Nohara et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the dysregulation of apoptosis leads to a variety of immune disorders, including immunodeficiency, tumorigenesis, allergies, and autoimmunity (Zhang et al, 2005). While several in vitro studies have been performed in order to identify chemically induced apoptosis in immunocytes (Nakadai et al, 2006;Li et al, 2007Li et al, , 2009Nohara et al, 2008), in vivo detection is difficult because of the rapid clearance of apoptotic cells by phagocytic cells (Savill, 1995a,b;Savill and Haslett, 1995;Kamath et al, 1997;Pryputniewicz et al, 1998). In this study, we attempt to develop a detection method of ex vivo environmental-or chemical-related thymic apoptosis using mouse primary thymocytes and a human acute T-cell leukemia cell line.…”
Section: Introductionmentioning
confidence: 99%
“…El arsénico inorgánico presente en el agua para consumo humano, es mucho más tóxico que el orgánico, llamado arsenobetaína, y que está presente en organismos marinos bivalvos, peces o algas marinas (Brown et al, 1990). Nohara et al (2008), describieron que el arsenito producía atrofia del timo induciendo una detención del ciclo celular y una disminución del peso del órgano. El timo, aunque su función disminuye con la edad, es indispensable para la activación de los linfocitos T, lo cual garantiza reacciones inmunes en diversas situaciones hasta la edad adulta tardía (Shanker, 2004).…”
Section: Introductionunclassified